Pengemasan Paket Wisata Edukasi Andaliman di Taman Eden 100 Kabupaten Toba, Sumatera Utara - Pakpahan, Rosdiana; Nainggola, Hetty Claudia (Rumah Jurnal UNEJ, 2024)
Taman Eden 100 Tourism Object is a tourist attraction that is very suitable as a tourist destination for people who live in the city. The beautiful atmosphere of natural scenery can help tourists who live in the city feel more calm and comfortable enjoying their vacation time. Currently, there are many travel agencies that package tourist objects that have the potential to become a tour package. To be able to compete with other tourist attractions, it is necessary to package tour packages that can adapt to tourists. Therefore, this study aims to produce a tour package based on the potentials that exist in the Taman Eden 100 Tourism Object. The research was conducted at Taman Eden 100, Toba Regency. The method used by the author in this study is a descriptive method with a qualitative approach. The data collection techniques in this research are in the form of literature study, observation, documentation, interviews and a check list with the Founder/Management of the Taman Eden 100 Tourism Object. The result of this research is